Analisis Puisi “Putra Putra Ibu Pertiwi” Karya Musthofa Bisri Sebagai Representasi Makna dalam Kajian Semantik dan Simbolik Bahasa Puisi - Wawan Hermawan; Amilatus Sholikah; Nur Kholida Hanum; Iktarna Faris Saufaqillah; Falah Arifbillah Subagio (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Mustofa Bisri's poem “Putra-Putra Ibu Pertiwi” shows the duality of Indonesian life through analysis of symbolism and deep meaning. The results show that there is a balance between good and bad, and morals are the determinants of life's journey. This poem has a social critique that shows how important it is to maintain moral principles amidst the difficulties faced by society today. This study enhances our understanding of the moral and social dynamics found in contemporary Indonesian literature and also expands our understanding of semantics and symbolics in literature.